2020
DOI: 10.1002/pssa.201900888
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure High‐Temperature Single‐Crystal Diamond Type IIa Characterization for Particle Detectors

Abstract: Various samples of multisectoral high‐pressure high‐temperature (HPHT) single‐crystal diamond plate (IIa type) (4 × 4 × 0.53 mm) are tested for particle detection applications. The samples are investigated by X‐ray diffractometry, photoluminescence spectroscopy, Raman spectroscopy, Fourier‐transform infrared, and visible/ultraviolet (UV) absorption spectroscopy. High crystalline perfection and low impurity concentration (in the {100} growth sector) are observed. To investigate detector parameters, circular 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Furthermore, it was found that there were obvious nitrogen-related optical characteristics in the monophonic region (1 of 400-1400 cm) by FTIR spectrum test (Nicolet iS50, Thermo Scientific, Waltham, MA, USA). Therefore, it accords with the characteristics of type Ib monocrystalline diamond [20,21], with dimensions of 3 × 3 × 1 mm 3 . The substrate was placed on the three-dimensional X-, Y-, and Z-axis removable workpiece stage of a laser system, which comprised a Nd:YAG (Neodymium Doped Yttrium Aluminum Garnet) laser (Lee Laser Inc., Orlando, FL, USA) and a 50 W high-power supply.…”
Section: Methodssupporting
confidence: 60%
“…Furthermore, it was found that there were obvious nitrogen-related optical characteristics in the monophonic region (1 of 400-1400 cm) by FTIR spectrum test (Nicolet iS50, Thermo Scientific, Waltham, MA, USA). Therefore, it accords with the characteristics of type Ib monocrystalline diamond [20,21], with dimensions of 3 × 3 × 1 mm 3 . The substrate was placed on the three-dimensional X-, Y-, and Z-axis removable workpiece stage of a laser system, which comprised a Nd:YAG (Neodymium Doped Yttrium Aluminum Garnet) laser (Lee Laser Inc., Orlando, FL, USA) and a 50 W high-power supply.…”
Section: Methodssupporting
confidence: 60%
“…It is known that HPHT substrates possess high resistivities up to 10 14 Ω cm. 51 The measured resistivity after irradiation was approximately 5 × 10 −2 Ω cm. Linear I−V behaviors were obtained even without deposition of metallic electrodes.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…F is an additional applied correction factor for the limiting contour because of the finite rectangular shape. It is known that HPHT substrates possess high resistivities up to 10 14 Ω cm . The measured resistivity after irradiation was approximately 5 × 10 –2 Ω cm.…”
Section: Resultsmentioning
confidence: 98%
“…The It has been observed that the nitrogen incorporation during the growth process favors SPE from one-or twocolor centres. The presence of small amount of oxygen and boron together with nitrogen during the growth process either inhibit the formation of isolated NV − centres or not visible due to background luminescence (impurities and structural defects) in diamond matrix [12,22]. One-color centres in Sample-A may be visible due to its structural perfection as evident from intensity of 1 st order Raman line (figure 3(a)) and the presence of 2 nd order Raman peak (figure 3(b)).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from ZPL (575 nm) and Raman line (521 nm), a broad peak at 554 nm (2 nd order Raman band) is more intense in the Sample-A compared to Sample-B and Sample-C. The high contrast of the second-order Raman line in Sample-A appears due to minimal background luminescence (impurities and structural defects) and reduced surface contamination[12]. The PL spectrum shown in figure3(c) demonstrates the population of negatively charged nitrogen-vacancy (NV -) centres as indicated by ZPL at 637 nm along with broad phonon sideband ranging from 640 nm to 780 nm backgrounds.…”
mentioning
confidence: 89%